The Role of Teachers in Fostering Positive Behavior in Students at Islamic Boarding Schools - Rosyadi, Muhammad Ikhwan; Aryanti, Yosi; Rambe, Khairul Fadli (Ahlussunnah: Journal of Islamic Education, 2024)
This study aims to uncover the process of moral formation of students at the Darussalam Gontor Modern Islamic Boarding School, Campus 9, Sulit Air, Solok, and to identify various obstacles and supporting factors that influence it. This study is a field study with a qualitative approach. Data were collected through observation techniques, in-depth interviews, and documentation, and used the snowball sampling method in determining informants. Data sources include the Head of the Islamic Boarding School, the Boarding School Teacher Advisory Board (Syeikh Rayon), Senior Students (Mudabbir), and students residing in the Syanggit Dormitory. The results of the study indicate that the process of moral formation of students is carried out comprehensively through two main channels, namely education in the classroom through Islamic subjects rich in moral content, and educational activities outside the classroom such as sports, speeches, and worship activities that shape the character and personality of students. The obstacles faced in this process include differences in student backgrounds, limited time and supervision, lack of student discipline, motivational crisis, psychological pressure, and minimal support from parents. On the other hand, there are several supporting factors, such as synergy and collaboration between students, the Mudabbir (Islamic youth leader), and homeroom teachers, as well as the active involvement of parents and teachers in fostering students' morals. These findings provide an important starting point for future researchers exploring similar issues in broader contexts and issues.